Pulp properties of araucaria hunsteneii sapwood and heartwood / Saiful Hazmi Zainal Abidin - Zainal Abidin, Saiful Hazmi (2001)
A research on pulp properties of Araucaria hunsteneii sapwood and heartwood. Two types of woods are been selected to done a research for the pulp properties of Araucaria hunsteneii. The technique were done base on the TAPPI Standard Method. The properties of both types of woods had been discovered. There was a huge comparison between those two woods especially on the bulk result. Some how it still in arrange of paper products.